Strategies and Learning Models for Arabic Language Instruction Based on the Independent Curriculum for the Digital Native Generation - Firdaus, Ahmad Royhan; Mufidah, Nuril (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED), 2025)
The rapid development of digital technology has significantly influenced educational practices, particularly in language learning. The emergence of the digital native generation, who are highly familiar with technology and prefer interactive learning environments, requires a pedagogical transformation in Arabic language instruction. This study aims to analyze the appropriate strategies and learning models for Arabic language teaching within the framework of the Independent Curriculum (Kurikulum Merdeka) in Indonesia, adjusted to the characteristics of digital native learners. This research employed a qualitative descriptive approach using a literature review method. Data were collected from various academic sources published between 2015 and 2025, including peer-reviewed journals, books, and conference proceedings. The data analysis applied a critical and thematic content analysis to identify key concepts, patterns, and implications related to Arabic learning strategies and models compatible with the Independent Curriculum. The findings reveal that five learning models , P roject-Based Learning (PjBL), Problem-Based Learning (PBL), Inquiry-Based Learning (IBL), Discovery Learning (DL), and Cooperative Learning (CL ) are the most effective and relevant for fostering student-centered, collaborative, and technology-integrated Arabic learning. These models align with the 4C competencies emphasized in the Independent Curriculum: critical thinking, creativity, communication, and collaboration. Integrating digital media and interactive platforms not only enhances students’ linguistic proficiency (maharah lughawiyyah) but also improves their motivation, engagement, and problem-solving skills. In conclusion, this study highlights the necessity of implementing digital pedagogy in Arabic language learning to meet the learning needs of digital natives. The integration of technology-based, collaborative, and inquiry-oriented models supports the realization of meaningful, flexible, and future-oriented education in the era of the Independent Curriculum.